POS0624 EFFICACY AND SAFETY OF LEVILIMAB IN COMBINATION WITH METHOTREXATE IN SUBJECTS WITH ACTIVE RHEUMATOID ARTHRITIS: PHASE III, DOUBLE-BLIND, PLACEBO-CONTROLLED, RANDOMIZED TRIAL - Mazurov, V.; Korolev, M.; Kundzer, A.; Soroka, N.; Kastanayan, A.; Povarova, T.; Plaksina, T.; Antipova, O.; Kretchikova, D.; Smakotina, S.; Tciupa, O.; Raskina, T.; et al. (Annals of the rheumatic diseases, 2021)
Previously, the results of phase II AURORA clinical study of levilimab in subjects with active rheumatoid arthritis (RA) have been reported1. Here we report topline 24-weeks results of preliminary primary efficacy and safety analysis of phase 3 double-blind, placebo-controlled randomized clinical study (SOLAR). To confirm that levilimab in combination with methotrexate is superior to placebo in combination with methotrexate in achieving ACR20 at week 12 and low disease activity (LDA) at week 24 in subjects with methotrexate (MTX) resistant active RA. The study is ongoing at 21 clinical sites in Russia and Belarus. All randomized subjects have completed 24 weeks of study between November 2019 and January 2021. 154 adults, aged ≥18 years with the diagnosis of RA (ACR 2010) for at least 24 weeks, and confirmed disease activity at screening despite treatment with MTX for the last 12 weeks (in a stable dose 15-25 mg/week, for at least 4 weeks) were randomly assigned (2:1) to receive either levilimab (162 mg, SC, QW) + MTX (n=102) or placebo + MTX (n=52). The randomization and treatment allocation were carried out by a central computer-based system. Subjects, caregivers, and those assessing the outcomes were blinded to group assignment. The hypothesis of superiority of levilimab over placebo was tested for two co-primary efficacy outcomes: proportion of subjects who achieved ACR20 at week 12 and proportion of subjects who achieved LDA of RA (DAS28-CRP <3.2) at Week 24 of the study. For ethical reasons, subjects who haven't achieved minimal clinical response at week 12 (≥20% reduction in the number of tender/swollen joints; 66/68) received rescue therapy at the discretion of the Investigator, and all subsequent efficacy assessments for those were considered missing. For the primary efficacy analysis, subjects with missing data due to study discontinuation or rescue therapy prescription were considered non-responders (non-responder imputation, NRI). Otherwise, the analysis was performed on observed cases. Safety was assessed through monitoring of adverse events (AEs). The primary analysis was based on 149 randomized subjects (n=99 and n = 50) for ACR20 and 154 randomized subjects (n= 102 and n = 52) for LDA. 70/99 (71%) of subjects who received levilimab and 20/50 (40%) who received placebo achieved ACR20 response at week 12. The difference in proportion was 30% with a lower bound of 97.5% CI 12.8%; p=0.0003 (Pearson's chi-squared test). 53/102 (52%) of subjects received levilimab and 3/52 (6%) received placebo achieved LDA at week 24. The difference in proportion was 46% with a lower bound of 97.5% CI 31.2 %; p<0.0001 (Pearson's chi-squared test). The safety population included all subjects, who received investigational product (n=154). The most common adverse events (reported in ≥5% of subjects) in levilimab and placebo arms, respectively were: blood cholesterol increase (19% vs. 10%), ALT increase (11% vs. 8%), lymphocyte count decrease (9% vs. 8%), blood bilirubin increase (11% vs. 0%), blood triglycerides increase (9% vs. 2%), AST increase (7% vs. 4%), IGRA with M.tuberculosis antigen positive (5% vs. 6%), ANC decrease (8% vs. 0%). No deaths were occurred. The study confirmed superior efficacy of levilimab + MTX over placebo + MTX in subjects with MTX resistant active RA. No new safety signals were detected. Trial registration: Clinicaltrials.gov identifier NCT04397562 [1]Mazurov V, Zotkin E, Ilivanova E, et al. FRI0114 EFFICACY OF LEVILIMAB, NOVEL MONOCLONAL ANTI-IL-6 RECEPTOR ANTIBODY, IN COMBINATION WITH METHOTREXATE IN PATIENTS WITH RHEUMATOID ARTHRITIS: 1-YEAR RESULTS OF PHASE 2 AURORA STUDY. Annals of the Rheumatic Diseases 2020;79:637-638. We thank all contributors to the SOLAR clinical trial V Mazurov: None declared, Maxim Korolev: None declared, Alena Kundzer: None declared, Nikolaj Soroka: None declared, Aleksander Kastanayan: None declared, Tatyana Povarova: None declared, Tatyana Plaksina: None declared, Olga Antipova: None declared, Diana Kretchikova: None declared, Svetlana Smakotina: None declared, Oksana Tciupa: None declared, Tatiana Raskina: None declared, Tatyana Kropotina: None declared, Olga Nesmeyanova: None declared, Tatiana Popova: None declared, Ekaterina Dokukina Employee of: JSC BIOCAD, Aleksandra Plotnikova Employee of: JSC BIOCAD, Anton Lutskii Employee of: JSC BIOCAD, Arina Zinkina-Orihan Employee of: JSC BIOCAD